Study of Regulatory and Institutional Framework for the Relocation of the National Capital in Indonesia - Hidayat, Arif; Sugiarto, Laga; Sulistianingsih, Dewi; Rafli Ananta, Bintang; Abid A Syakur, Muhammad (Journal of Law and Legal Reform, 2024)
This study explores the regulatory and institutional framework for relocating Indonesia’s national capital (Ibu Kota Nusantara, IKN) from Jakarta to East Kalimantan, a plan rooted in the integrative ideology articulated by Soepomo in 1945. This ideology emphasizes harmony between macrocosmic and microcosmic forces within the state, suggesting that the government center should be located centrally within the country to symbolize supreme authority. The relocation is also seen as a crucial move toward achieving “Indonesia Emas 2045”. However, the enactment of Law No. 3 of 2022, which serves as the legal basis for the relocation, has faced significant criticism, particularly regarding the regulatory, institutional, and funding aspects. Previous studies have often been opinion-based and lacked scientific rigor, especially in addressing the complexities of policy implementation. This research aims to fill this gap by providing a detailed analysis of the policy from regulatory and institutional perspectives. The study uses a normative legal approach, incorporating both statute and conceptual analyses, to evaluate the regulatory and institutional frameworks guiding the capital relocation. While it does not extensively address funding issues, it focuses on identifying how well the existing rules align with the policy’s implementation goals. Findings suggest that while the relocation offers significant benefits, such as promoting national unity and symbolizing progress, the process faces challenges, including conflicts with existing regulations and institutional inefficiencies. The contribution of this study lies in offering actionable insights for both the government and civil society to assess and improve the policy’s implementation, ensuring its alignment with the broader vision of national development.